2020
DOI: 10.1186/s12905-020-01081-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and patterns of gender-based violence across adolescent girls and young women in Mombasa, Kenya

Abstract: Background We sought to estimate the prevalence and describe heterogeneity in experiences of gender-based violence (GBV) across subgroups of adolescent girls and young women (AGYW). Methods We used data from a cross-sectional bio-behavioural survey among 1299 AGYW aged 14–24 in Mombasa, Kenya in 2015. Respondents were recruited from hotspots associated with sex work, and self-selected into one of three subgroups: young women engaged in casual sex (YCS), young women engaged in transactional sex (YTS), and you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
33
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 34 publications
(48 reference statements)
7
33
1
Order By: Relevance
“…Another study conducted in Menkorer High school, North west Ethiopia indicated that Respondents with current educational status of good and above were less likely to be a victim of gender based violence by nine Percent when compared with students who have poor educational status (5). Another study conducted in Mombasa, Kenya showed that literacy decreased gender based violence's (19).…”
Section: Associated Factors Of Gender Based-violencementioning
confidence: 99%
“…Another study conducted in Menkorer High school, North west Ethiopia indicated that Respondents with current educational status of good and above were less likely to be a victim of gender based violence by nine Percent when compared with students who have poor educational status (5). Another study conducted in Mombasa, Kenya showed that literacy decreased gender based violence's (19).…”
Section: Associated Factors Of Gender Based-violencementioning
confidence: 99%
“…Domestic violence is a vicious, silent epidemic that is ravaging society at an increasingly alarming rate if the recent statistics regarding the vice are anything to go by. About 30 percent of women across the world have witnessed or experienced domestic violence in terms of physical or sexual intimate partner violence, while 7 percent have experienced non-partner violence (Bhattacharjee et al, 2020). More specifically, the rates of domestic violence in Sub-Saharan Africa are regarded as one of the highest in the world (Otolo, 2020).…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…In such societies, women are encouraged to consider, tolerate, and rationalise domestic violence as an integral component of their culture. This is supported by cultural beliefs that are deeply entrenched and women who go against them risk facing embarrassment and guilt (Bhattacharjee et al, 2020). It has therefore become increasingly difficult for data regarding the prevalence of domestic violence to be collected in Kenya, largely because the vice is still accepted as a cultural practice or considered a private affair that should not be reported to the authorities (Otolo, 2020).…”
Section: Cultural Norms and Valuesmentioning
confidence: 99%
See 2 more Smart Citations